TAX PLANNING ANALYSIS FOR THE EFFICIENCY OF INCOME TAX AGENCY (STUDY OF PT ABDYA GASINDO) - Rizkina, Miftha; Junawan, Junawan (Accounting and Business Journal, 2021)
The purpose of this paper is to determine whether the implementation of tax planning by PT. Abdya Gasindo can streamline corporate income tax. The writing method used is descriptive method, namely the method that collects, collects the data obtained and then interpreted and analyzed so that it is able to provide complete information for problem solvers at hand. The results of this study are expected to be able to provide information and input to Abdya Gasindo so that the company can carry out tax planning as an effort to improve tax payment efficiency to achieve maximum profit, but still within the framework of taxation regulations. The conclusion of this research is the implementation of tax planning by PT. Abdya Gasindo can streamline the tax burden payable.